FO/MD hybrid system for real dairy wastewater recycling. Issue 18 (17th September 2018) - Song, Hongwei; Xie, Fang; Chen, Weiwei; Liu, Jinrong
ABSTRACT: This study investigated a forward osmosis and membrane distillation (FO/MD) hybrid system for real dairy wastewater (DWW) recycling. Two types of FO membranes, cellulose triacetate-embedded polyester screen support (CTA-ES) and aquaporin inside (AQP), were employed. Sodium chloride was used as the draw solution. A cross-flow FO cell and an air gap membrane distillation module were established to conduct individual FO experiments and FO/MD experiments. From the experiments, an analysis of the water flux ( Jw ), reverse draw solute flux ( Js ), Js /Jw ratio and contaminant rejection was performed. The reverse draw solute flux was determined by monitoring the chlorine ions in the feed solution of the FO process. The study demonstrated that real DWW could be reclaimed by the FO/MD hybrid system for the reuse of urban recycled water or for higher grade utilization. The DWW flux was influenced by feed foulants, the fouling stage as well as membrane properties. Furthermore, the Js /Jw ratios were lower and more invariable for the CTA-ES membrane than for the AQP membrane, suggesting that the CTA-ES membrane had superior filtration performance. A fouled CTA-ES membrane could recover 90% of the flux after membrane cleaning.